Comparative study of evolution of structured flows at boundary of the regime change “diffusion — concentration convection” in isothermal multicomponent mixing in gases by techniques of visual and numerical analysis - В.Н. Косов; С.А. Красиков; С.М. Белов; O.В. Федоренко; М. Жанели (Қарағанды университетінің хабаршысы. Физика сериясы)
During isothermal multicomponent diffusion process, the number of effects appear that are not observed visually when mixed in binary mixtures. These include occurrence of convective instability with subsequent formation of structured flows. The feature of this type of mixing is that convection is realized under conditions of decrease in density of mixture with height. Flow visualization method allows to fix information about distribution of medium parameters by dynamics of structures in convective flows. Application of computer processing methods, as well as techniques of identifying images of thermophysical fields, allows to obtain quantitative information about convective flows. For an isothermal ternary gas mixture heliumargonnitrogen, shadow images of structural formations formed in convective flows due to the instability of mechanical equilibrium are represented in this work. To carry out digital analysis of experimental shadow images, a simplified virtual model of the lower chamber of the diffusion cell was created. Based on digital analysis of visual images, quantitative characteristics related to estimation of the size of convective formations, period of their formation, and linear velocity of convection cells when moving through diffusion channel are presented. It has been established that the growing convective disturbances arising in the system cause a change in the characteristic scale of convective cells. The analysis of shadow images also showed that a vortex is formed in convective flows, which consists mainly of a component with the highest molecular weight. Comparison of visual images of experimental fields with simulation flows is implemented, on the basis of which composition of mixture components in convective structures is estimated. It is shown that the obtained value of the concentration of the heavy component in the vortex filament can be taken as the minimum.